Body Composition, Dermatoglyphics and Aerobic Resistance in Sub-20 Category Footballers from Bogota, Colombia - Erazo Bello, Juan Sebastián (2021)
Soccer has generated endless research that has enhanced athlete’s qualities to achieve maximum sports performance. According to the above, the use of new tools has been implemented to improve talent selection processes and develop physical abilities, as is the case with dermatoglyphics that provides information on an individual’s genotype. The present study aims to relate body composition, dermatoglyphics, and maximum oxygen consumption in soccer players’ category sub-20. The research had a quantitative, non-experimental, cross-sectional design. The sample comprised 22 players (age 18±1.1) from Bogota Sports Club, Colombia. They were assessed for body composition, the somatotype was calculated, handprints were analyzed, and the maximum oxygen consumption was measured with the Test Course Navette. The results show a predominance of balanced mesomorph somatotype (53%), high presence of “L” ridges (66.36 %), low presence of “A” arches (1.82%), and maximum oxygen consumption of 53.76±3.73 ml/kg/min. Furthermore, significant relationships were found between D10-SCTL dermatoglyphic components and the endomorph somatotype (p <0.05), and between the maximum VO₂ with endomorph and ectomorph somatotype (p <0.05). It is concluded that soccer players are characterized by having a predisposition towards coordination, resistance, and agility.